Multi-objective quantum-behaved particle swarm optimization for economic environmental hydrothermal energy system scheduling - Feng, Zhong-kai; Niu, Wen-jing; Cheng, Chun-tian (Energy (Oxford), 2017)
With increasing attention paid to energy and environment in recent years, the hydrothermal scheduling considering economic and environmental objectives is becoming one of the most important optimization problems in power system. With two competing objectives and a set of operation constraints, the economic environmental hydrothermal scheduling problem is classified as a typical multi-objective nonlinear constrained optimization problem. Thus, in order to efficiently resolve this problem, the multi-objective quantum-behaved particle swarm optimization (MOQPSO) is presented in this paper. In MOQPSO, the elite archive set is adopted to conserve Pareto optimal solutions and provide multiple evolutionary directions for individuals, while the neighborhood searching and chaotic mutation strategies are used to enhance the search capability and diversity of population. Furthermore, a novel constraint handling method is designed to adjust the constraint violation of hydro and thermal plants, respectively. In order to verify its effectiveness, the MOQPSO is applied to a classical hydrothermal system with four hydropower plants and three thermal plants. The simulations show that the proposed method has competitive performance compared with several traditional methods. •Multi-objective quantum-behaved particle swarm optimization is proposed.•Mutation and neighborhood search enhance the population diversity.•Constraints handling method improves the feasibility of individuals.•MOQPSO obtains better solutions with less fuel cost and emissions.